(untitled) (Research, Society and Development, 2021)
Introduction: Actions to promote women’s health must be offered in a holistic, participatory, individual and collective way, in all areas. Considering that women should be guided on self-care so that, in a conscious and autonomous way, they manage their health care. Objective: To report the experience in carrying out a health education action, referring to women’s health. Methodology: Descriptive study, the type of experience report, carried out by Nursing students at UFJ, regarding the Woman OAB event. Results and Discussion: The event took place in March 2019, with lectures, a health and beauty fair, legal and psychological space, children’s space, lunch and leisure opening at the Thermas club. In the project there were the participation of ten students and two professors of the Nursing course, educational practices were developed regarding family planning, safe sex, STIs prevention, teenage pregnancy, self-care and the importance of a healthy lifestyle and debate about violence. Conclusion: The event provided the students the contact with the social reality of the participants, enabling reflection with regard to humanization in women’s health and the u nderstanding of practices based on dialogue, welcoming and collective construction.